Simple steps to enable reproducibility: culture conditions affecting Chlamydomonas growth and elemental composition. (11th July 2022) - Hui, Colleen; Schmollinger, Stefan; Strenkert, Daniela; Holbrook, Kristen; Montgomery, Hayden R.; Chen, Si; Nelson, Hosea M.; Weber, Peter K.; Merchant, Sabeeha S.
SUMMARY: Even subtle modifications in growth conditions elicit acclimation responses affecting the molecular and elemental makeup of organisms, both in the laboratory and in natural habitats. We systematically explored the effect of temperature, pH, nutrient availability, culture density, and access to CO2 and O2 in laboratory‐grown algal cultures on growth rate, the ionome, and the ability to accumulate Fe. We found algal cells accumulate Fe in alkaline conditions, even more so when excess Fe is present, coinciding with a reduced growth rate. Using a combination of Fe‐specific dyes, X‐ray fluorescence microscopy, and NanoSIMS, we show that the alkaline‐accumulated Fe was intracellularly sequestered into acidocalcisomes, which are localized towards the periphery of the cells. At high photon flux densities, Zn and Ca specifically over‐accumulate, while Zn alone accumulates at low temperatures. The impact of aeration was probed by reducing shaking speeds and changing vessel fill levels; the former increased the Cu quota of cultures, the latter resulted in a reduction in P, Ca, and Mn at low fill levels. Trace element quotas were also affected in the stationary phase, where specifically Fe, Cu, and Zn accumulate. Cu accumulation here depends inversely on the Fe concentration of the medium. Individual laboratory strains accumulate Ca, P, and Cu to different levels. All together, we identified a set of specific changes to growth rate, elemental composition, and the capacity to store Fe in response to subtle differences in culturing conditions of Chlamydomonas, affecting experimental reproducibility. Accordingly, we recommend that these variables be recorded and reported as associated metadata. Significance Statement: The reproducible cultivation of organisms is of crucial importance for their use in any scientific or biotechnological application. Temperature, pH, nutrients, culture density and efficient gas exchange are among the most important growth parameters for cultivating algae. Iron is an essential cofactor for oxygenic photosynthesis, and consequently growth limiting to crop plants and algae when absent. Iron storage sites are important for detoxification, metabolic remodeling and for the competitiveness of an organism in iron‐poor environments.